The Malacca Strait : will it continue to be safe? - Ho, Joshua (2011)
The Republic of Singapore Navy issued an unprecedented advisory last week for shipping to improve security measures while transiting the Malacca Strait. It shows the continued need for vigilance despite the many security measures implemented so far.